Effects of a six-week exercise intervention on function, pain and lumbar multifidus muscle cross-sectional area in chronic low back pain: A proof-of-concept study. (October 2020) - Lindsay, K.; Caplan, N.; Weber, T.; Salomoni, S.; De Martino, E.; Winnard, A.; Scott, J.; Young, E.; Hides, J.; Hodges, P.W.; Debuse, D.
Abstract: Introduction: Exercise with the Functional Re-adaptive Exercise Device (FRED) has previously been shown to activate the lumbar multifidus (LM) and transversus abdominis (TrA) muscles in non-symptomatic volunteers. This study aimed to determine the effects of a six-week FRED exercise intervention on pain intensity, patient-reported function and LM cross sectional area (CSA) in people with chronic non-specific low back pain (LBP). Methods: Thirteen participants undertook six weeks of FRED exercise for up to 15 min, three times per week. At six weeks pre-, immediately pre-, immediately post-, and six and 15 weeks post-intervention, participants completed the Numeric Pain Rating Scale, Patient-Specific Functional Scale, and ultrasound imaging was used to assess the size of the LM muscles at L5 level. Changes in outcomes were assessed using effect size, confidence intervals and minimum clinically important difference (MCID). Results: There was no improvement in pain intensity following the intervention. Patient-reported function improved by at least twice the MCID for all follow-up assessments compared to immediately pre-intervention (d = 4.20–6.58). Lumbar multifidus CSA showed a large effect size increase from immediately pre-intervention to immediately post-intervention (d = 0.8–1.1); this was maintained at six weeks post-intervention (not measured at 15 weeks post-intervention). Conclusion: Six weeks of FRED exercise improved physical function in all 13 participants with chronic non-specific LBP who took part in this study and most participants' lumbar multifidus muscle CSA. On this basis, it may be an effective intervention for people with chronic LBP and should now be tested in a randomised controlled trial. Highlights: Exercise intervention for LBP effective in people with chronic LBP. PSFS scores up to 3x MCID greater after exercise intervention for chronic LBP. Large ES increase in Lumbar Multifidus muscle cross sectional area in chronic LBP. 6 weeks 3 × 15 min exercise per week enough to return to function with chronic LBP.